Pengetahuan Mengenai Infeksi Menular Seksual dan Status Kesehatan Reproduksi : Studi pada Narapidana Lapas Kelas IIA Yogyakarta - Muhammad Zaitun Fathurachman (Pancanaka, 2022)
Adequate knowledge about Sexually Transmitted Infections (STIs) and reproductive health in general is important to be understood and applied by prison inmates. This study provides an overview of the reproductive health status of Class IIA Yogyakarta prison inmates. This cross-sectional study used a descriptive analytic design, conducted in February 2022 with 49 inmates of the Yogyakarta Class IIA Prison Special Region of Yogyakarta as research subjects. The majority of respondents were in the age group of 20-39 years with a mean age of 23.9 ± 5.94. A total of 87.8% of respondents have knowledge of Sexually Transmitted Infections (STI) and 87.8% of respondents also have knowledge of HIV/AIDS. A total of 42.8% of respondents had more than one sexual partner before serving their incarceration term, and only 13.3% of respondents always used condoms during sexual intercourse. There is no access for prisoners to obtain condoms or other contraceptive services in prison. Respondents knowledge of STIs and HIV/AIDS is quite good, but the use of condoms is relatively minimal compared to their knowledge. There is no comprehensive health care system in prison that handles the various reproductive health needs of prisoners.